2016
DOI: 10.1021/acs.chemmater.6b03098
|View full text |Cite
|
Sign up to set email alerts
|

Shape Control of Colloidal Cu2–xS Polyhedral Nanocrystals by Tuning the Nucleation Rates

Abstract: Synthesis protocols for colloidal nanocrystals (NCs) with narrow size and shape distributions are of particular interest for the successful implementation of these nanocrystals into devices. Moreover, the preparation of NCs with well-defined crystal phases is of key importance. In this work, we show that Sn(IV)-thiolate complexes formed in situ strongly influence the nucleation and growth rates of colloidal Cu2–xS polyhedral NCs, thereby dictating their final size, shape, and crystal structure. This allowed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 74 publications
(199 reference statements)
4
32
0
Order By: Relevance
“…[148,181] However, the presence of cations can also influence the shape of the NC. [182] For example Chen et al [183] demonstrated a morphological evolution of the Cu 31 S 16 nanodisks to tetradecahedra due to the Sn 4+ -directed modification of the vertical crystal planes of the copper sulfide disk seeds. This leads to the preferential deposition of the copper and sulfur source on the vertical crystal planes, favoring the formation of the tetradecahedra.…”
Section: [12]mentioning
confidence: 99%
“…[148,181] However, the presence of cations can also influence the shape of the NC. [182] For example Chen et al [183] demonstrated a morphological evolution of the Cu 31 S 16 nanodisks to tetradecahedra due to the Sn 4+ -directed modification of the vertical crystal planes of the copper sulfide disk seeds. This leads to the preferential deposition of the copper and sulfur source on the vertical crystal planes, favoring the formation of the tetradecahedra.…”
Section: [12]mentioning
confidence: 99%
“…Copper sulfide (Cu 2−x S, 0< x < 1), a non-toxic and conductive chalcogen compound, has been continuously noted for its excellent photoelectric behavior, potential thermal/electrical properties, and unique biomedical properties for decades, and much extensive research on Cu 2−x S micro/nano structures is still being actively conducted. In particular, micro/nanostructured Cu 2−x S with well-controlled shapes, sizes, structures and compositions have already been applied as photocatalytic materials [1], energy conversion materials [2], biosensing materials [3], and bioimaging materials [4] and have shown reasonable results. However, comprehensive reviews of the Cu 2−x S structure in-depth in applications are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The easily tunable crystal structure of Cu 2– x S nanocrystals results in a wide variety of sizes and shapes attainable for Cu 2– x S nanocrystals by a proper choice of reaction conditions during colloidal synthesis. 12 , 13 Furthermore, depending on the size and shape of the Cu 2– x S nanocrystals and the Cu to S ratio, Cu 2– x S nanocrystals possess highly tunable localized surface plasmon resonances (LSPR) in the near-infrared (NIR) spectral region. 6 , 14 16 The LSPR in copper chalcogenide nanomaterials originates from excess holes in the top of the valence band, 6 , 15 , 17 which are compensated by Cu + deficiencies in the lattice.…”
Section: Introductionmentioning
confidence: 99%